2012
DOI: 10.1289/ehp.1103634
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Phthalates and Phenols during Pregnancy and Offspring Size at Birth

Abstract: Background: Data concerning the effects of prenatal exposures to phthalates and phenols on fetal growth are limited in humans. Previous findings suggest possible effects of some phenols on male birth weight.Objective: Our aim was to assess the relationships between prenatal exposures to phthalates and phenols and fetal growth among male newborns.Methods: We conducted a case–control study on male malformations of the genitalia nested in two French mother–child cohorts with recruitment between 2002 and 2006. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
249
12
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(290 citation statements)
references
References 30 publications
(43 reference statements)
27
249
12
2
Order By: Relevance
“…Tier 2 included 13 publications. Twelve of those publications (Wolff et al , 2010(Wolff et al , 2015Philippat et al 2012Philippat et al , 2014Watkins et al 2015;Aker et al 2016;Ashley-Martin et al 2016;Buckley et al 2016;Lassen et al 2016;Smarr et al 2017;Geer et al 2017) were based on seven different cohorts assembled in France, Puerto Rico, Denmark, Canada, and various parts of the US. One paper ) presented a case-control study that used incident cases identified among members of a French cohort.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tier 2 included 13 publications. Twelve of those publications (Wolff et al , 2010(Wolff et al , 2015Philippat et al 2012Philippat et al , 2014Watkins et al 2015;Aker et al 2016;Ashley-Martin et al 2016;Buckley et al 2016;Lassen et al 2016;Smarr et al 2017;Geer et al 2017) were based on seven different cohorts assembled in France, Puerto Rico, Denmark, Canada, and various parts of the US. One paper ) presented a case-control study that used incident cases identified among members of a French cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 43 studies, 24 were conducted in North America (Wolff et al , 2010(Wolff et al , 2015Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al 2015;Ihde et al 2015;Shiue 2015aShiue , 2015bVelez et al 2015;Ashley-Martin et al 2016;Buckley et al 2016;Poole et al 2016;Scinicariello and Buser 2016;Smarr et al 2017;Geer et al 2017), two studies in the Caribbean (Watkins et al 2015;Aker et al 2016), 10 studies in Europe (Allmyr et al 2009;Chevrier et al 2012;Philippat et al 2012Philippat et al , 2014Bertelsen et al 2013;Buhl et al 2014;Den Hond et al 2013, 2015Geens et al 2015;Lassen et al 2016), four in Asia (Chen et al 2013;Wang et al 2015;Xue et al 2015;Zhu et al 2016), and three in Australia (Cullinan et al 2012(Cullinan et al , 2015a…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…151 Other studies have reported similar results in spite of weak statistical evidence that phthalates increase a child's weight. [152][153][154] While most phthalate research has focused on children in the United States, one cross-sectional study was conducted in three primary and three middle schools in China. The Chinese researchers found that, when age and sex were included in the model, MEHP and MEP were positively associated with BMI and WC.…”
Section: Metalsmentioning
confidence: 99%
“…A questionnaire was designed that included characteristics of a baby either at or near birth or well after birth, or that did not describe a particular life stage. We included characteristics that have been suggested by human research to be affected by different EDCs, as indicated by asterisks on Table II -namely: incomplete masculinization of boy children (Swan et al, 2005;Marsee et al, 2006); obesity (Eng et al, 2013); asthma (Vaidya & Kulkarni, 2012); intelligence (Cho et al, 2010); behavior (Kim et al, 2009); fertility (Cantonwine et al, 2013); and birth weight (Philippat et al, 2012). The average percentage of women who agreed that characteristics around birth defined the healthy baby was 69%, compared with 40% agreeing that later characteristics applied, and 56% agreeing that characteristics without a defined time applied.…”
Section: The Healthy Babymentioning
confidence: 99%